2013
DOI: 10.1111/and.12102
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of pituitary adenylate cyclase-activating polypeptide (PACAP) in the human testis and in testicular germ cell tumors

Abstract: Pituitary adenylate cyclase-activating peptide (PACAP) is a neuropeptide expressed in the central nervous system and peripheral organs. Previous studies revealed the role and distribution of PACAP in the rodent testis, however, its presence in the human testis and in testicular germ cell tumors is not known. We used RT-PCR and immunohistological observations to investigate whether human testicular tissue and testicular germ cell tumors contain PACAP. The mRNAs for PACAP and its receptors were detected in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
0
27
1
2
Order By: Relevance
“…We did not find significant differences between normal and tumoral tissue samples. In contrast with results of Nakamura et al (2014), we did not recognize significant alterations between seminoma and embryonal tumoral samples.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not find significant differences between normal and tumoral tissue samples. In contrast with results of Nakamura et al (2014), we did not recognize significant alterations between seminoma and embryonal tumoral samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Our research group reported that PACAPdeficient mice have an abnormal sperm morphology and PACAP increases sperm motility in human spermatozoa indicating the important role of PACAP in sperm motility and fertilization (Brubel et al 2012). Recently, Nakamura et al (2014) have shown that the mRNA for PACAP and its receptors are expressed in human testis. They also described the localization of PACAP immunoreactivity in normal and tumoral testicular samples.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This protective effect is one of its most promising features for therapeutic use, even considering the short half-life in vivo [10,11]. In the last decade, increasing amount of evidence has emerged regarding the important roles of PACAP in peripheral organs such as uterus [12], ovary [13], testis [14], moreover its presence has been proved in human milk [15]. Nonetheless, only sporadic data exist about its function in skeletal elements [16][17][18].…”
Section: Pituitary Adenylate Cyclase Activating Polypeptide (Pacap) Amentioning
confidence: 99%
“…PACAP and its receptors are widely expressed in the testis (Agnese et al, ; Agnese, Valiante, Rosati, Andreuccetti, & Prisco, ; Arimura et al, ; Rosati et al, , ). First evidence of the presence of PACAP in the testis has been reported in mammals, and, in particular, in rat spermatogonia, primary spermatocytes, and spermatids (Hannibal & Fahrenkrug, ; Shioda et al, ); further investigations confirmed the presence of PACAP in the human testis at the level of spermatogonia and round spermatid (Nakamura et al, ), as well as in mouse epididymal sperm acrosome (Tanii, Aradate, Matsuda, Komiya, & Fuse, ). No evidence of PACAP was reported in somatic cells, that is, Sertoli and Leydig cells (Arimura et al, ; Miyata et al, ; Shioda et al, ).…”
Section: Introductionmentioning
confidence: 95%